A CORRELATIONAL STUDYON THEIMPACT OF STUDENTS’ ENGLISH ACHIEVEMENT ON STUDENTS’ RESIDENCE - Putra, Muhammad Iqbal Ripo; ., Sulaiman (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2017)
The purposes of this research are to reveal: (1) the students‘English achievement; (2) the relationship between students‘ residenceand students‘ English achievement; and (3) the significant relationshipbetween students‘ residence and students‘ English achievement. Theresearchers used correlational research design as the design of thisresearch. The population of this research is 112 students of the tenthgrade of SMAN 1 Silat Hulu and the total number of sample are 60students who are chosen by using stratified sampling technique. Theinstruments used questionnaire and documentation. Based on the resultof research finding and discussion in this research, it can be concludedthat the average of English achievement of the students‘ who live withparents was higher than the students who live with no-relative and thereare a significant correlation between students‘ residence and students‘English achievement. Key word: students‟ residence, students‟ English achievement, correlational research